Flexural elastic buckling stress of batten type light gauge built-up member = Sprężyste naprężenia krytyczne zgięciowej formy wyboczenia wbudowanych, dwugałęziowych słupów przewiązkowych wykonanych z lekkich elementów cienkościennych - Mitsui, Kazuya; Sato, Atsushi (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In Japan, built-up member composed with light gauge is used for studs of shear wall. Flexural buckling stress of built-up compression member is evaluated by effective slenderness ratio. The effective slenderness ratio of light gauge built-up compression member is proposed for heavy sections; however, it is not verified that it can be adopted in light gauge.
Keywords: thin-walled elements; thin-walled column; elastic stresses; critical stresses; elementy cienkościenne; lekki przekrój cienkościenny; element wbudowany; naprężenia krytyczne